Music in dreams: a diary study - König, Nina; Schredl, Michael (Psychology of music, 2021)
In every culture and nation music has been mentioned as a sort of natural language. While the existence of dreams including music in musicians has been anecdotally reported, music in dreams have been rarely studied empirically. In the present study, 425 participants, mostly psychology students, reported their dreams in a dream diary for 14 days as well as the intensity of their dream emotions and answered a questionnaire about whether they play existing music or compose new music during the day. As expected, for persons playing an instrument in their leisure time, there was a direct link between playing an instrument during the day and having more dreams including music, thus confirming the continuity hypothesis of dreaming. In addition, dreams including music were more positively-toned regarding emotions than dreams in general. Further research might investigate, for example, whether dreams including music play a role in improving music performance skills.
Article first published online: June 29, 2019
Gesehen am 05.10.2021